2020
DOI: 10.1097/ijg.0000000000001735
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Spin in the Abstracts of Systematic Reviews and Meta-analyses of Treatments for Glaucoma

Abstract: Purpose: Spin—the misrepresentation of the study’s actual findings—carries the ability to distort a reader’s perception of a treatments’ full benefits and risks. Recent studies have suggested that spin is common in abstracts of randomized controlled trials and systematic reviews focused on treatments for a variety of medical disorders. Therefore, our primary objective was to evaluate the prevalence of spin in the abstracts of systematic reviews and meta-analyses related to glaucoma treatments. We f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 19 publications
3
1
0
Order By: Relevance
“…Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract 33 . However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%) 36 32…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract 33 . However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%) 36 32…”
Section: Discussionsupporting
confidence: 79%
“…32 Similarly, Reddy et al found that 36% of systematic reviews on rotator cuff management contained spin in their abstract. 33 However, percentages of abstracts containing spin from other medical specialties and disorders were similar to that of ours: smoking cessation (3.5%), 34 ophthalmology (2.9%), 35 and otolaryngology (10%). 36 While our findings showed lower amounts of spin compared to systematic reviews in other fields, the most common spin types were similar to the findings of Ottwell and colleagues who also found the two most prevalent spin types to be types three and five.…”
Section: Primary Findingssupporting
confidence: 79%
“…Our team's previous investigations found spin in abstracts at rates ranging from 37% in oncology RCTs [18] to 70% in otolaryngology RCTs [37]. More recently, studies have shown that spin frequently occurs in abstracts of systematic reviews [38][39][40][41][42][43][44][45][46][47][48]. As previously mentioned, Ottwell et al [20] identified spin in 31% of the included abstracts of systematic reviews and meta-analyses on acne vulgaris therapies, a finding similar to ours.…”
Section: Xsl • Fosupporting
confidence: 86%
“…When comparing the presence of spin in abstracts of systematic reviews from the field of dermatology with other specialties, dermatology-focused systematic reviews appear to contain more spin in the abstract than systematic reviews focused on tinnitus and glaucoma therapies. 29,30 However, systematic reviews from the field of dermatology appear to contain less spin than systematic reviews focused on therapies for lower back pain. 31 For example, Nascimento et al 31 found that 80% (53/66) of systematic reviews focused on low-back pain treatments contained spin.…”
Section: Commentmentioning
confidence: 99%